Design of an Internet of Things (IoT) based Main Reservoir Water Level Measuring Device at Siti Hajar Hospital Sidoarjo - Adi Winarno; Rochman, Sagita; Nanda, Bagus (BEST, 2026)
The volume of water levels in hospital water reservoirs really requires full monitoring. Where water reservoirs often run out when the water is to be used. This is very fatal and hinders activities that must be carried out immediately. If this happens, it will result in the failure of ongoing activities at the hospital. This research aims to design a prototype that is capable of monitoring water levels in IoT-based hospital reservoirs. By designing a water level monitoring system in the reservoir using the HC-SR04 ultrasonic sensor as an input that measures water level and ESP32 as a microcontroller. The application produced from MIT App Inventor is a notification output and can display monitoring results. Based on the research results, it shows that the water level monitoring system in the reservoir can work well as expected, namely when the water is at the 25% limit, the application will send a notification to the smartphone in the form of sound so that users or technicians can find out and find the cause of the decreasing water level.